Triple-Jump Assessment Model for Use of Evidence-Based Medicine - Monica Bhutiani; William M. Sullivan; Sandra Moutsios; Elizabeth Ann Yakes; Jennifer K. Green; Kimberly Lomis; William B. Cutrer (Association of American Medical Colleges, 2016)
Abstract Introduction A vital element of health care practice is evidence-based medicine, the explicit and judicious use of current, best-available evidence in making decisions about the individualized care of patients. With the use of evidence-based medicine continually increasing in clinical practice, medical schools are charged with ensuring graduates are prepared to appropriately access, appraise, and utilize clinical evidence, highlighting the need for a corresponding assessment tool. However, assessing evidence-based practice remains a challenging endeavor for medical educators. Few assessment tools capture students' ability to apply information resources in order to answer a targeted question during a medical encounter. Methods We describe a triple-jump assessment design where students access evidence, appraise information at hand, and apply it to formulate a treatment plan during an observed structured clinical encounter (OSCE). Results One hundred and five clerkship students participated in one of two OSCE scenarios. Data from this exercise underwent descriptive statistical analysis, including mean performance scores and confidence scores, and showed that accuracy and confidence in providing evidence-based care improved after the search and appraisal period. Discussion The addition of a modified triple-jump assessment to the end of the OSCE experience not only creates a more authentic experience but also allows for assessment and development of student metacognitive skills within the domain of knowledge gap assessment. The ease of integrating this assessment into the structure of an already-developed OSCE allows for different types of assessment to be achieved without writing entirely new OSCE cases, but rather by modifying existing scenarios.